Measurement of the Effects of School Psychological Services: A Scoping Review - Müller, Bettina; von Hagen, Alexa; Vannini, Natalie; Büttner, Gerhard (Frontiers in Psychology, 2021)
School psychologists are asked to systematically evaluate the effects of their work to ensure quality standards. Given the different types of methods applied to different users of school psychology measuring the effects of school psychological services is a complex task. Thus, the focus of our scoping review was to systematically investigate the state of past research on the measurement of the effects of school psychological services published between 1998 and 2018 in eight major school psychological journals. Of the 5,048 peer-reviewed articles published within this period, 623 were coded by two independent raters as explicitly refering to school psychology or counseling in the school context in their titles or abstracts. However, only 22 included definitions of effects of school psychological services or described outcomes used to evaluate school psychological services based on full text screening. These findings revealed that measurement of the effects of school psychological services has not been a focus of research despite its’ relevance in guidelines of school psychological practice.